1986
DOI: 10.1038/bjc.1986.110
|View full text |Cite
|
Sign up to set email alerts
|

Second primary neoplasms in patients with retinoblastoma

Abstract: Summary In a series of 882 retinoblastoma patients, 384 known to have the genetic form of the disease and 498 others, 30 patients developed second primary neoplasms. The spectrum of these second neoplasms is discussed in relation to the forms of treatment used for the retinoblastoma. Cumulative incidence rates of second tumours in the whole series are 2.0% at 12 years after diagnosis and 4.2% after 18 years. For patients with the genetic form of retinoblastoma the cumulative incidence rate after 18 years is 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
240
2
4

Year Published

1993
1993
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 526 publications
(252 citation statements)
references
References 28 publications
(30 reference statements)
5
240
2
4
Order By: Relevance
“…[65] The elevated risk of second primary bladder cancer among retinoblastoma survivors has been attributed to radiation treatment or cyclophosphamide chemotherapy [66][67][68]. However, Fletcher et al, found that hereditary retinoblastoma survivors who were not exposed to highdose radiation or chemotherapy had a substantially higher mortality from bladder cancer versus the general population (standardized mortality ratio [SMR] = 26.3; 95%, CI 8.5-61.4).…”
Section: High-penetrance Genesmentioning
confidence: 99%
“…[65] The elevated risk of second primary bladder cancer among retinoblastoma survivors has been attributed to radiation treatment or cyclophosphamide chemotherapy [66][67][68]. However, Fletcher et al, found that hereditary retinoblastoma survivors who were not exposed to highdose radiation or chemotherapy had a substantially higher mortality from bladder cancer versus the general population (standardized mortality ratio [SMR] = 26.3; 95%, CI 8.5-61.4).…”
Section: High-penetrance Genesmentioning
confidence: 99%
“…Individuals harbouring germline mutations in the Rb gene and who have retinoblastoma as children show an increased risk of melanoma as adults (Draper et al, 1986;Traboulsi et al, 1988;Eng et al, 1993;Bataille et al, 1995). In addition, three melanoma prone families have been reported to possess germline mutations in the CDK4 gene that cosegregate with the disease.…”
Section: Abstract: Familial Melanoma; Cdk6mentioning
confidence: 99%
“…This 'two hit' mechanism was first hypothesised by Knudson (Knudson, 1976) and later substantiated following cloning of RB1 (Friend et al, 1986). In patients with germline mutations, bilateral Rb tumours usually develop and patients have an increased risk of secondary cancers, in particular osteosarcoma and soft tissue sarcoma (Draper et al, 1986;Roarty et al, 1988). In the sporadic unilateral Rb tumours, both RB1 mutations are required in the same somatic cell to initiate tumour formation.…”
mentioning
confidence: 93%